Dynamic contrast-enhanced MRI for monitoring bisphosphonate therapy in Paget’s disease of bone - Libicher, Martin; Kasperk, Christian; Daniels-Wredenhagen, Mark; Heye, Tobias; Kauczor, Hans-Ulrich; Nawroth, Peter Paul; Delorme, Stefan; Hosch, Waldemar P. (Skeletal radiology, 2013)
The purpose of this study was to evaluate changes in regional bone perfusion in Paget’s disease (PD) following bisphosphonate therapy. We used dynamic contrast-enhanced MRI (DCE-MRI) for assessment of bone perfusion and compared MRI findings with alkaline phosphatase (AP) as a serum marker of bone turnover.
Published online: 16 May 2012
Gesehen am 01.03.2022